2021
DOI: 10.3389/fpls.2021.793459
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Sulfotransferase-Involving Strigolactone Biosynthetic Route in Sorghum

Abstract: LOW GERMINATION STIMULANT 1 (LGS1) plays an important role in strigolactones (SLs) biosynthesis and Striga resistance in sorghum, but the catalytic function remains unclear. Using the recently developed SL-producing microbial consortia, we examined the activities of sorghum MORE AXILLARY GROWTH1 (MAX1) analogs and LGS1. Surprisingly, SbMAX1a (cytochrome P450 711A enzyme in sorghum) synthesized 18-hydroxy-carlactonoic acid (18-hydroxy-CLA) directly from carlactone (CL) through four-step oxidations. The further … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…However, five MAX1 homologues have been identified in the rice genome ( Zhang et al , 2014 ), while more recent studies showed that the presence of multiple MAX1 genes is a common characteristic in grasses. More specifically, maize has three MAX1 genes ( Yoneyama et al , 2018 ), sorghum has four ( Wu and Li, 2021 ), and B. distachyon has five ( Changenet et al , 2021 ). According to some studies, MAX1s from grasses fall into four different clades ( Marzec et al , 2020 ; Wu and Li, 2021 ), whereas Vinde et al (2022) only accounted for the presence of three separate groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, five MAX1 homologues have been identified in the rice genome ( Zhang et al , 2014 ), while more recent studies showed that the presence of multiple MAX1 genes is a common characteristic in grasses. More specifically, maize has three MAX1 genes ( Yoneyama et al , 2018 ), sorghum has four ( Wu and Li, 2021 ), and B. distachyon has five ( Changenet et al , 2021 ). According to some studies, MAX1s from grasses fall into four different clades ( Marzec et al , 2020 ; Wu and Li, 2021 ), whereas Vinde et al (2022) only accounted for the presence of three separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, maize has three MAX1 genes ( Yoneyama et al , 2018 ), sorghum has four ( Wu and Li, 2021 ), and B. distachyon has five ( Changenet et al , 2021 ). According to some studies, MAX1s from grasses fall into four different clades ( Marzec et al , 2020 ; Wu and Li, 2021 ), whereas Vinde et al (2022) only accounted for the presence of three separate groups. The multiple MAX1 homologues have been suggested to catalyse different steps in the conversion of CL to bioactive SL molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond arabidopsis, the pathway downstream of carlactone to generate different structures of canonical strigolactones may entail, for example, several paralogues of the CYP711A MAX1 cooperating sequentially, as in rice (Yoneyama et al, 2018 ; Y. Zhang et al, 2014 ). It may also recruit, downstream of MAX1 orthologues, other CYP450 enzymes such as CYP722C isoforms in cotton ( Gossypium arboretum ), tomato ( Solanum lycopersicum ) and cowpea ( Vigna unguiculata ) (Wakabayashi et al, 2019 , 2020 ), or the CYP728B35 LOW GERMINATION STIMULANT1 (LGS1) in sorghum ( Sorghum bicolour ) (Gobena et al, 2017 ; Wu & Li, 2021 ). The CYP712G1 enzyme of tomato was very recently shown to oxidize orobanchol to didehydro‐orobanchol isomers, one of which can be further converted to solanacol (Y. Wang, Durairaj, et al, 2022 ).…”
Section: Latest Developments In the Synthesis Perception And Transpor...mentioning
confidence: 99%